PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN RAJA UDUK PONTIANAK - Sarina Sarina; Eva Dolorosa; Imelda Imelda (Jurnal Sains Pertanian Equator, 2018)
Growing number of restaurant lead to intense competition in the culinary business. A proper marketing strategy is necessary to win the competition. The purpose of this research is to analyze marketing mix (the product, the price, the place, and the promotion) of purchasing decisions in the Raja Uduk restaurant Pontianak. This research used survey method with the quantitative analysis that is Structural Equation Modelling (SEM) by soffware LISREL 8.80. The respondents in this study as many as 150 which were taken by accidental sampling. Research results show that the product influence significanty the consumer purchasing decisions with the t-value 2.10 > 1.96. The prices do not affect significantly to consumer purchasing decisions with the t-value 0.49 < 1.96. The place has no affect significantly to consumer purchasing decisions with the t-value 0,23 < 1.96. The promotion influence significantly to consumer purchasing decisions with the t-value 3.09 > 1.96